1995
DOI: 10.1046/j.1471-4159.1995.65030978.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase‐Activating Polypeptide (PACAP) Regulation of Sympathetic Neuron Neuropeptide Y and Catecholamine Expression

Abstract: Two forms of pituitary adenylate cyclase-activating polypeptide (PACAP), the 38-and 27-amino-acid forms (PACAP38 and PACAP27, respectively), which share amino acid sequence homology with vasoactive intestinal peptide (VIP), were evaluated for their abilities to regulate sympathetic neuron catecholamine and neuropeptide Y (NPY) expression . PACAP38 and PACAP27 potently and efficaciously stimulated NPY and catecholamine secretion in primary cultured superior cervical ganglion (SCG) neurons; 100-to 1,000-fold hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 39 publications
6
37
0
Order By: Relevance
“…In addition, PACAP is found in preganglionic sympathetic neurons in the intermediolateral cell column of the thoracolumbar spinal cord and accordingly, PACAPergic fibers densely innervate sympathetic ganglia. Postganglionic sympathetic neurons selectively express PAC1 receptors at high levels and PACAP potently stimulates sympathetic NPY and catecholamine release, which has implicated PACAP peptides as one of the noncholinergic regulators of sympathetic function (21, 35). Congruently, PACAP is colocalized with acetylcholine in abdominal preganglionic splanchnic nerve terminal terminals innervating the adrenal medulla for epinephrine release.…”
Section: Pacap and The Stress Responsementioning
confidence: 99%
“…In addition, PACAP is found in preganglionic sympathetic neurons in the intermediolateral cell column of the thoracolumbar spinal cord and accordingly, PACAPergic fibers densely innervate sympathetic ganglia. Postganglionic sympathetic neurons selectively express PAC1 receptors at high levels and PACAP potently stimulates sympathetic NPY and catecholamine release, which has implicated PACAP peptides as one of the noncholinergic regulators of sympathetic function (21, 35). Congruently, PACAP is colocalized with acetylcholine in abdominal preganglionic splanchnic nerve terminal terminals innervating the adrenal medulla for epinephrine release.…”
Section: Pacap and The Stress Responsementioning
confidence: 99%
“…The PAC 1 HOP1 receptor, by contrast, is dually coupled to Gα s and Gα q/11 to potently and efficaciously stimulate adenylate cyclase, phospholipase C, mitogen-activated protein kinase (MAPK), and other intracellular effectors that in aggregate have the potential of generating diverse cellular response (2, 1012). Recent studies, for example, have shown that the PAC 1 HOP receptor isoform coupling to phospholipase C for calcium mobilization and influx is essential for neurotransmitter/neuropeptide release (13, 14). PAC 1 HOP1 receptor overexpression in embryonic cortical neurons results in phospholipase C activation, PKC translocation, and cellular calcium flux to facilitate proliferation (9, 15).…”
Section: Introductionmentioning
confidence: 99%
“…To examine the abilities for PACAP/PAC 1 receptor signaling to engage and coordinate these events in one neuronal system, we have employed primary sympathetic neurons that we have shown previously to preferentially express the PAC 1 HOP1 receptor isoform (13, 37, 38). All of the highly conserved members of the MAPK family, including ERK1 and ERK2 (p44 and p42, respectively), ERK5, JNK, and p38 MAPK, have been well described to participate in neuronal development, differentiation, cell cycle progression, and survival; how PAC 1 HOP1 receptor signaling impacts one or all of the MAPKs is not known.…”
Section: Introductionmentioning
confidence: 99%
“…PACAP is expressed throughout the central and peripheral nervous systems, where it exerts effects on neurite outgrowth (Deutsch et al 1993), neuropeptide and neurotransmitter production (May and Braas 1995), and neuronal proliferation (Lu and DiCicco-Bloom 1997;Villalba et al 1997). The diverse activities of PACAP are mediated by multiple-target tissue receptors.…”
Section: Introductionmentioning
confidence: 99%